1975
DOI: 10.1111/j.1365-2389.1975.tb01964.x
|View full text |Cite
|
Sign up to set email alerts
|

The High‐ and Low‐energy Phosphate Adsorbing Surfaces in Calcareous Soils

Abstract: The two-surface Langmuir equation was used to study P adsorption by 24 calcareous soils (pH 7-27.6; 0-8-24.2 per cent CaCO,) from the Sherborne soil series, which are derived from Jurassic limestone. High-energy P adsorption capacities ( x; ) ranged from 140-345 pg P/g and were most closely correlated with dithionite-soluble Fe. Hydrous oxides therefore appear to provide the principal sites, even in calcareous soils, on which P is strongly adsorbed (k' = 6-51 ml/pg P). The low-energy adsorption capacities ( x;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
63
0
1

Year Published

1982
1982
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 113 publications
(66 citation statements)
references
References 22 publications
2
63
0
1
Order By: Relevance
“…Much of the adsorption attributed to it, however, may actually be due to hydrous ferric oxide impurities". Holford and Mattingly (1975) have also shown that, in calcareous soils, free iron oxides were the main soil variable related to the high-energy phosphate-adsorbing surface and the low-energy P adsorbents were correlated with organic matter and surface area of calcium carbonate. Similarly, concluded that Al ox and Fe ox were the best variables to explain P sorption capacities in neutral and calcareous soils from Québec.…”
Section: Suitability Of P Saturation Indices For P Management In Québmentioning
confidence: 99%
“…Much of the adsorption attributed to it, however, may actually be due to hydrous ferric oxide impurities". Holford and Mattingly (1975) have also shown that, in calcareous soils, free iron oxides were the main soil variable related to the high-energy phosphate-adsorbing surface and the low-energy P adsorbents were correlated with organic matter and surface area of calcium carbonate. Similarly, concluded that Al ox and Fe ox were the best variables to explain P sorption capacities in neutral and calcareous soils from Québec.…”
Section: Suitability Of P Saturation Indices For P Management In Québmentioning
confidence: 99%
“…The P sorption affinity, P adsorption maxima and EPR values were much lower in these soils than in the soils under CT. The low biodegradation of these high contents of organic matter may have, as some of its products, humic substances such as organic acid anions such as citrate and tartarate whose concentrations in the rhizosphere may reach a level high enough to enable them compete strongly with phosphate anions for adsorption sites on reactive surfaces of solid constituents such as oxides of Fe and Al (Holford and Mattingly, 1975 ), but greater amounts are found in the rhizosphere of crop plants (Vance et al, 1996). It has been observed that the organic acids (the tri-carboxylic and di-carboxylic acids) that most commonly occur in soils are effective in reducing phosphate sorption, whereas monocarboxylic acids have little effect on phosphate sorption (Hingston et al, 1971;Earl et al, 1979;Yuan, 1980;Sibanda and Young, 1986;Violante et al, 1991Violante et al, , 1996.…”
Section: Soil Organic Mattermentioning
confidence: 99%
“…Nevertheless, the acceptance in the literature of these multisite ideas has been highly contested. For example, Syers et al (1973), Holford et al (1974), Mattingly (1975), andShuman (1975) proposed that a two-surface Langmuir equation (that is, a combination of two Langmuir equations) can be used to accurately describe ion adsorption by soils. Posner and Bowden (1980), however, criticized this approach and stated that it should not be used "unless there is some a priori reasoning for doing so."…”
Section: Competitive and Multisite Adsorption Modelsmentioning
confidence: 99%